Metabolic and Gut Microbiota Responses to Sourdough Pasta Consumption in Overweight and Obese Adults - Shah, Shrushti; Brown, Paul D. S.; Mayengbam, Shyamchand; Gänzle, Michael G.; Wang, Weilan; Mu, Chunlong; Lettrari, Silvio; Bertagnolli, Craig; Shearer, Jane (Frontiers in Nutrition, 2020)
Increasing consumer interest in fermented products has driven the emergence of a number of novel foods including shelf-stable sourdough pasta. This study comprehensively examined the impact of fermentation on the microbial composition of the culture, pasta, its subsequent effects on glycemic responses and gut microbiota in overweight men and women (>25 kg/m2) compared to a conventional, non-fermented pasta. Two, randomized crossover trials were performed. Study A examined acute feeding responses to each product wherein fasted participants completed a meal tolerance test comprised of 75 g of conventional or sourdough pasta to examine glycemic responses. Results showed enhanced gastric emptying with sourdough, but no difference in overall blood glucose, insulin or satiety hormone responses between the treatments. Study B consisted of three standard oral glucose tolerance tests as well as fecal collection for sequencing at baseline and following each pasta intervention (150 g or 2 serving/d for 5 days) followed by a 2-week washout period. Results showed no differential impact of either pasta treatment on glucose tolerance. Analysis of fecal bacterial and fungal (mycobiome) microbiota showed no change at the individual species or genus levels. However, fungi were adaptive following chronic pasta consumption with decreases in alpha diversity of fungi following sourdough, but not conventional pasta. This was accompanied by reductions in total fecal short chain fatty acid concentrations. In conclusion, sourdough fermentation did not change the overall glycemic properties of the pasta, incretin responses or bacterial gut microbiota, but appears to impact microbiome fungal community structure with chronic consumption.